2020
DOI: 10.1038/s41598-020-73626-8
|View full text |Cite
|
Sign up to set email alerts
|

HMGR overexpression and interference affect the expression of steroidogenic genes and cholesterol content in bovine intramuscular adipocytes

Abstract: Previously, we found that mevalonic acid stimulates 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGR) expression in bovine intramuscular adipocytes to influence adipocyte differentiation. However, any direct links among HMGR, steroidogenic genes, and cholesterol content remain unclear. RNA-Seq was conducted to determine the differences between the gene expression profiles of bovine adipocytes containing different HMGR expression constructs. In total, 10,234 differentially expressed genes (DEGs) were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It has been reported that the polymorphisms of the HMGCR gene were associated with several lipid deposition- and cholesterol-related traits, and also with IMF content of gluteus medius muscle in pigs ( Canovas et al, 2010 ; Chalupová et al, 2012 ). In bovine intramuscular adipocytes, the alteration of the HMGCR gene could affect the expression abundance of AMP-activated protein kinase (AMPK) and sirtuin type 1 (SIRT1), which exert important roles in the regulation of energy metabolism ( Lin et al, 2020 ). The polymorphisms in the 3′UTR of the HMGCR gene exhibited significant association with the total cholesterol content in chicken muscle.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the polymorphisms of the HMGCR gene were associated with several lipid deposition- and cholesterol-related traits, and also with IMF content of gluteus medius muscle in pigs ( Canovas et al, 2010 ; Chalupová et al, 2012 ). In bovine intramuscular adipocytes, the alteration of the HMGCR gene could affect the expression abundance of AMP-activated protein kinase (AMPK) and sirtuin type 1 (SIRT1), which exert important roles in the regulation of energy metabolism ( Lin et al, 2020 ). The polymorphisms in the 3′UTR of the HMGCR gene exhibited significant association with the total cholesterol content in chicken muscle.…”
Section: Discussionmentioning
confidence: 99%
“…3-Hydroxy-3-Methylglutaryl-CoA reductase (HMGR) is a rate-limiting enzyme for cholesterol synthesis. Transcriptional and pathway analysis results showed that the overexpression of HMGR was correlated with the down-regulation of AMPK gene expression ( Lin et al, 2020 ). Schisandra chinensisfruit (SF) extract may decrease lipid accumulation by up-regulating lipolytic factors (AMPK) and decreasing the expression or activity of lipogenic modulators (HMGR) ( Liu et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…This protein can catalyze the conversion of 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG-CoA) to mevalonate and is a key factor in the regulation of cholesterol content in vivo. 40 In addition, Fab-4 is predominantly expressed in adipocytes and macrophages and plays a significant role in the development of IR, and atherosclerosis and is also known as intracellular lipid chaperones that control lipid mobilization and responses in cells. 41 In the current study, we found that supplementation of HFD to rats significantly upregulated the mRNA and protein expressions of PPAR-γ, SREBP-1c, FAS, HMG-CoA reductase, and Fab-4.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HMG‐CoA reductase is a rate‐limiting enzyme of cholesterol synthesis. This protein can catalyze the conversion of 3‐hydroxy‐3‐methyl‐glutaryl‐coenzyme A (HMG‐CoA) to mevalonate and is a key factor in the regulation of cholesterol content in vivo 40 . In addition, Fab‐4 is predominantly expressed in adipocytes and macrophages and plays a significant role in the development of IR, and atherosclerosis and is also known as intracellular lipid chaperones that control lipid mobilization and responses in cells 41 .…”
Section: Discussionmentioning
confidence: 99%